3D OBJECTS CREATION APPROACH FOR AR PROJECTS (Computer systems and information technologies, 2021)
In this paper are discussed the application of 3D technologies, which are reflected in various areas of life, such as education, science, engineering and entertainment industry. The use of 3D technology in the educational process can significantly increase its efficiency by bringing the virtual computer environment closer to the real three-dimensional world. But for now the use of augmented reality in teaching is only gaining momentum. Many applications are still quite primitive, but developers are actively working on their refinement, increasing the amount of educational content, improving quality. The task of fast and high-quality algorithm for creating 3D content for further import in AR training projects has been urgent. The aim of this work is to increase the level of use of 3D technologies in the educational process for an effective and external interactive way of providing information. In the course of the work the methods of creating 3D content for different areas of application such as game industry, 3D visualization, 3D printing, AR projects, holographic fans, preliminary assessment of technical properties of the product and etc were considered. Data analysis has been shown that for each area of ​​application 3d content has its own requirements and features.  This information was identified and presented in the form of a comparative table.  Based on the analysis of modern methods of developing 3D content for various applications, a general method of creating 3D objects for further import into AR projects was proposed. Based on the proposed approach, a 3D model of the character for the children audio-encyclopedic stories educational application was designed. The obtained models were also integrated in the augmented reality environment. The use of this approach has increased the download speed of the model in an augmented reality application.